Synthesis and characterisation of silver(I) halo-pyridyl compounds: a study of the prominent NCIs that govern crystal packing - Theunissen, Tristan (Department of Chemistry, 2026)
This study aimed to identify which non-covalent interactions (NCIs) would dominate in the solid-state structures of silver(I) halopyridyl compounds. Five novel compounds were synthesised and several metal involved NCIs were observed. The five compounds which formed a cohesive series are: [Ag2(OBn)2], [Ag2(2 Pic)2(OBn)2], [Ag2(3-Clpy)2(OBn)2], [Ag2(2-Brpy)2(OBn)2], and [Ag2(2-Ipy)2(OBn)2]. X-ray diffraction analysis of single crystals constituted the solid-state study portion of the NCIs. Their influence on the crystal structure was carried out using modern computational techniques, such as molecular electrostatic surface potential (MESP), natural bond orbital or NBO analysis, and quantum theory of atoms in molecules (QTAIM). This dissertation comprises four sections, the first of which introduces background knowledge on particular topics such as crystal engineering, non-covalent interactions, and possible applications that NCIs have within crystal engineering and supramolecular chemistry. The second and third sections discuss specific methods and techniques used to study the NCIs from a crystallographic and computational viewpoint. The final section summarises the contribution of the authors' work to the understanding and body of knowledge of NCIs. As shown in this dissertation, the ‘self-assembled' [Ag2(OBn)2(Xpy)2] compounds are closely related to their strongest non-covalent metal-involved interactions, such as AgI···π, AgI···X, and AgI···AgI, while also being influenced by weaker interactions', π···π, cooperativity effects. The importance of orbital-based charge transfers as opposed to being purely electrostatic in the argentophilicity of compounds I-V has been discussed. In this study, quantitative QTAIM, NBO, and MEPS-based analyses were carried out on the metallophilic (M+···M+) interactions. The computational studies suggest a greater role of orbital-based interactions in the strength and distance of said interactions. This hypothesis was applied to other NCIs, such as semi-coordination and metal-π NCIs, in which orbital-based charge-transfers are also shown to predominate force stabilising the compounds over pure electrostatic interactions. Compounds VI-VIII, although not included within the main series (I-V) display a variety of similar NCIs, as evident from their single-crystal structures, whose natures or characteristics are formed from the foundations of computations I-V. Prominent NCIs are AgI···π, AgI···X, and AgI···AgI, which are also influenced by weaker interactions', π···π, cooperativity effects.